PREPARATION AND CHARACTERIZATION OF CO-CRYSTALS OF DIACEREIN - Thenge, Raju Rameshrao; Patond, V B; Ajmire, P V; Barde, L N; Mahajan, N M; Tekade, N P (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2017)
Diacerein, anti-inflammatory drug used in the treatment of osteoarthritis. Being a BCS class II drug, it has poor solubility, dissolution rate and other physicochemical properties. Thus the aim of present study was to prepare co-crystals of diacerein to improve solubility, dissolution rate. The diacerein co-crystals were prepared using urea and tartaric acid as conformer by Solvent drop grinding method. The diacerein co-crystals were characterized by scanning electron microscopy (SEM), FT-IR spectroscopy (FT-IR), Differential scanning calorimetry (DSC) and X-ray diffractometry (XRD). The co-crystals were evaluated for solubility, dissolution rate and other physicochemical properties and compared with commercial diacern sample. The co-crystals exhibit the difference in the size and shape of crystals. The FT-IR spectra of diacerein co-crystals showed slightly different in the characteristic peaks compared to commercial diacerein sample. DSC data indicate the decrease in the melting endotherm of co-crystals compare to diacerein. The co-crystals with urea showed increase and intense peak and co-crystals with tartaric acid showed decreased number of peaks compared to commercial diacerein. The co-crystals of diacerein formulated in to the Tablet and evaluated for tablet properties. The tablet formulation showed improved tablet characteristics as well as dissolution rate compared to commercial diacerein.